2015
DOI: 10.1249/01.mss.0000480423.93457.28
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Two Brief Physical Activity Questionnaires with Accelerometers among African American Women

Abstract: Aim-To evaluate the validity of the Stanford Brief Activity Survey (SBAS) and Exercise Vital Sign (EVS) questionnaire against accelerometer-determined time in moderate-to-vigorous physical activity (MVPA) among African-American (AA) women.Background-Limited research has evaluated the validity of brief physical activity (PA) questionnaires among AA women. Since the validity of PA questionnaires may differ among members of varying racial/ethnic groups, research is needed to explore the validity of self-report PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Study participants were all adults; ages ranged from 18 to 89 years. Most studies were of mainly Caucasian populations, although one study examined EVS tool use in African‐American women (Joseph, Keller, Adams, & Ainsworth, ). No studies of EVS or PAVS tool use in adolescent or pediatric populations were identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study participants were all adults; ages ranged from 18 to 89 years. Most studies were of mainly Caucasian populations, although one study examined EVS tool use in African‐American women (Joseph, Keller, Adams, & Ainsworth, ). No studies of EVS or PAVS tool use in adolescent or pediatric populations were identified.…”
Section: Resultsmentioning
confidence: 99%
“…No studies of EVS or PAVS tool use in adolescent or pediatric populations were identified. Five studies examining the EVS tool were identified (Coleman et al., ; Fitzgerald, Ozemek, Jarrett, & Kaminsky, ; Grant, Schmittdiel, Neugebauer, Uratsu, & Sternfeld, ; Joseph et al., ; Young, Coleman, Ngor, Reynolds, Sidwell, & Sallis, . Tool psychometrics were reported in all five of these studies, and implementation of the EVS was also discussed in two of these studies (Coleman et al., ; Grant et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Self-reported physical activity < 150 min per week, which aligns with public health recommendations. We used the Physical Activity Vital Sign (PAVS) [20][21][22][23][24][25], which includes the following two questions: 1. "On average, how many days a week do you engage in moderate to strenuous exercise (like a brisk walk)?"…”
Section: Participants and Recruitmentmentioning
confidence: 99%
“…The selected age range focuses tailoring of the intervention to the social, cultural, and behavioral characteristics of young to middle-aged adult AA women who, among all AA women, are the most likely to own smartphones [47]. Women are eligible to participate if they: a) selfidentify as AA; b) are aged 24 to 49 years; c) have a BMI ≥30 kg m 2 d) have insufficient levels of PA, defined as performing <60 minutes/week of MVPA according to the 2-item Exercise Vital Sign questionnaire, which has been previously validated against accelerometers for assessment of PA among AA women [48]; and e) have the ability to speak and read English. Exclusion criteria include: a) concurrent participation in another PA, nutrition, or weight loss program at time of enrollment or any time during the 8-month study; b) indication of a potential contraindication of exercise according to the 2015 Physical Activity Readiness Questionnaire (PAR-Q+) [49], unless a written permission from the potential participant's primary care physician is provided; c) pregnant at time of screening or plans to become pregnant in the next 8 months; and d) plans to relocate out of the Phoenix metropolitan area in the next 12 months.…”
Section: Samplementioning
confidence: 99%